(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2024)
Agriculture has been neglected most of these years. investment, if any, has been centered at low-productive units and mis-targeted subsidiaries. minimum support prices (MSP) for crops given to farmers has didn't provide enough profits on the hands of farmers to shop for two-time meals, neglect about the leisure of 24-hour power and water supply.To enhance situations of farmers, the authorities will have to emphasis on irrigation, improvement of rainfed agriculture, merchandising of integrated farming, excessive-price agri-produce, and many others. at the same time, diversification beyond vegetation into horticulture, greens, livestock, rooster and fisheries, etc followed with the aid of the improved investment in seeds can also be required. “similarly, the studies sector needs to be bolstered in order that incredible irrigation procedures may be advanced within the country itself. Greater centres for agricultural studies need to additionally be opened and college students want to be recommended to pursue profession paths of agricultural scientists. The government should additionally attract investments in agriculture so that scientific techniques can bolster the united states’s crop manufacturing,”